Gymnodinium baicalense and Gymnodinium coeruleum (Dinophyta) outbreaks in Lake Baikal - Karnaukhov, D.; Zausaeva, N.; Ermolaeva, Ya.; Dolinskaya, E.; Biritskaya, S.; Teplykh, M.; Silenko, N.; Shimaraeva, S.; Silow, E. (Acta Biologica Sibirica, 2019)
This paper presents data on the abundance of the two most abundant dinophytic algae species Gymnodinium baicalense and Gymnodinium coeruleum recorded in the spring of 2019. Data on the accumulation thickness of the planktonic algae over the different depths are presented.